Necrostatin-1: a promising compound for neurological disorders - Chen, Ke-qian; Wang, Shu-zhi; Lei, Hai-bo; Liu, Xiang (Frontiers in Cellular Neuroscience, 2024)
Necrostatin-1, a small molecular alkaloid, was identified as an inhibitor of necroptosis in 2005. Investigating the fundamental mechanism of Necrostatin-1 and its role in various diseases is of great significance for scientific and clinical research.Accumulating evidence suggests that Necrostatin-1 plays a crucial role in numerous neurological disorders. Regrettably, Necrostatin-1 has not been completely reviewed in the treatment of neurological disorders. Therefore, this paper reviews the potential functions of Necrostatin-1 in various neurological disorders. This review aims to provide a comprehensive overview of the potential functions of Necrostatin-1 in various neurological disorders, offering valuable insights for future research.